2023
DOI: 10.3390/mi14050941
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of g-C3N4/TCNQ Composite and Photocatalytic Degradation of Pefloxacin

Abstract: g-C3N4 and g-C3N4/TCNQ composites with different doping levels were prepared using the copolymerization thermal method with melamine as a precursor. XRD, FT-IR, SEM, TEM, DRS, PL, and I-T characterized them. The composites were successfully prepared in this study. The photocatalytic degradation of pefloxacin (PEF), enrofloxacin (ciprofloxacin), and ciprofloxacin (ciprofloxacin) under visible light (λ > 550 nm) showed that the composite material had the best degradation effect on PEF. When TCNQ doping is 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This showed that different ligands also affect the structure of the MOF materials. The characteristic peaks of MIL-100(Fe) mainly appeared at 2θ degrees of 10.2° and 11.0° [27], and the characteristic peaks of the g-C3N4 were around 27.5°, which correspond to the crystalline diffraction peaks of raw g-C3N4 [28].…”
Section: Xrd Analysismentioning
confidence: 93%
“…This showed that different ligands also affect the structure of the MOF materials. The characteristic peaks of MIL-100(Fe) mainly appeared at 2θ degrees of 10.2° and 11.0° [27], and the characteristic peaks of the g-C3N4 were around 27.5°, which correspond to the crystalline diffraction peaks of raw g-C3N4 [28].…”
Section: Xrd Analysismentioning
confidence: 93%
“…Besides, the NU90TC10 composite showed broader photon adsorption regions, which was attributed to the existence of TCNQ in NU90TC10, improving its photon response ability. 67 The photocatalytic elimination mechanism of Cr(VI) over NU90TC10 was verified through photocurrent responses, photoluminescence (PL) and electrochemical impedance spectroscopy (EIS) measurements. 68 First, to deepen the understanding of the photo-generated carrier separation behaviour, photocurrent response curves for NH 2 -UiO-66, TCNQ and NU90TC10 were measured during on/off light illumination (Fig.…”
Section: Photocatalytic Performancesmentioning
confidence: 98%